2014
DOI: 10.1111/ajo.12231
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body weight and first trimester screening for chromosomal anomalies

Abstract: Prenatal risk ratios for Down syndrome adjust for maternal weight because maternal serum biomarker levels decrease with increasing maternal weight. This is accomplished by converting serum biomarker values into a multiple of the expected median (MOM) for women of the same gestational age. Weight is frequently not recorded and the impact of using MOMs not adjusted for weight for calculating risk ratios is unknown. The aim of this study is to examine the effect of missing weight on first trimester Down syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…A similar result for PAPP-A was obtained in Australia, where it was found an inverse relation between maternal BMI and the values of free β-HCG and PAPP-A. 33 Spencer et al 18 also found a direct relation between PAPP-A and gestational age. Moreover, the presence of trisomy 21 has been associated with lower levels of PAPP-A and higher levels of free β-HCG.…”
Section: Discussionsupporting
confidence: 62%
“…A similar result for PAPP-A was obtained in Australia, where it was found an inverse relation between maternal BMI and the values of free β-HCG and PAPP-A. 33 Spencer et al 18 also found a direct relation between PAPP-A and gestational age. Moreover, the presence of trisomy 21 has been associated with lower levels of PAPP-A and higher levels of free β-HCG.…”
Section: Discussionsupporting
confidence: 62%